Growth hormone therapy in children; research and practice – A review. (February 2019) - Collett-Solberg, Paulo Ferrez; Jorge, Alexander A.L.; Boguszewski, Margaret C.S.; Miller, Bradley S.; Choong, Catherine Seut Yhoke; Cohen, Pinchas; Hoffman, Andrew R.; Luo, Xiaoping; Radovick, Sally; Saenger, Paul
Abstract: Short stature remains the most common reason for referral to a pediatric Endocrinologist and its management remains a challenge. One of the main controversies is the diagnosis of idiopathic short stature and the role of new technologies for genetic investigation of children with inadequate growth. Complexities in management of children with short stature includes selection of who should receive interventions such as recombinant human growth hormone, and how should this agent dose be adjusted during treatment. Should anthropometrical data be the primary determinant or should biochemical and genetic data be used to improve growth response and safety? Furthermore, what is considered a suboptimal response to growth hormone therapy and how should this be managed? Treatment of children with short stature remains a "hot" topic and more data is needed in several areas. These issues are reviewed in this paper. Highlights: Endocrinologists should be familiar with gene technologies to assess short stature. The diagnosis of milder forms of growth hormone deficiency remains a challenge. Adequate monitoring of the efficacy and safety of GH should remain a priority.